2012
DOI: 10.1177/026119291204000208
|View full text |Cite
|
Sign up to set email alerts
|

The Comparability of In Vitro and Ex Vivo Studies on the Percutaneous Permeation of Topical Formulations Containing Ibuprofen

Abstract: In order to avoid in vivo experiments and to gain information about the suitability of surrogates for skin replacement, Franz-type diffusion cell experiments were conducted by using three ibuprofen-containing formulations (cream, gel and microgel) on bovine split-skin samples and cellophane membranes. Moreover, ex vivo examinations were performed on the isolated perfused bovine udder, to study the comparability of in vitro and ex vivo experimental set-ups. Depending on the formulation, noticeable differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…At intervals of 15, 30, 60, 90, 120, 180, 240, 300, and 360 minutes, a sample (1 mL) was taken o u t a n d e v a l u a t e d u s i n g a U V-V i s i b l e Spectrophotometer at 273 nm. In order to keep the sink condition, fresh PBS pH 6.8 (2 mL) was introduced to replace the removed sample (32)(33)(34)(35)(36)(37).…”
Section: Ex-vivo Permeation Studiesmentioning
confidence: 99%
“…At intervals of 15, 30, 60, 90, 120, 180, 240, 300, and 360 minutes, a sample (1 mL) was taken o u t a n d e v a l u a t e d u s i n g a U V-V i s i b l e Spectrophotometer at 273 nm. In order to keep the sink condition, fresh PBS pH 6.8 (2 mL) was introduced to replace the removed sample (32)(33)(34)(35)(36)(37).…”
Section: Ex-vivo Permeation Studiesmentioning
confidence: 99%
“…Comparative studies between different ibuprofencontaining formulations demonstrated the impact of the formulation on the amount of ibuprofen within the skin (skin absorption) (Stahl et al 2011(Stahl et al , 2012. Comparative studies between different ibuprofencontaining formulations demonstrated the impact of the formulation on the amount of ibuprofen within the skin (skin absorption) (Stahl et al 2011(Stahl et al , 2012.…”
Section: The Influence Of Formulations On Drug Diffusion Into and Thrmentioning
confidence: 99%
“…Comparative studies between different ibuprofencontaining formulations demonstrated the impact of the formulation on the amount of ibuprofen within the skin (skin absorption) (Stahl et al 2011(Stahl et al , 2012. Other commercially available 5 % ibuprofen-containing formulations (cream, gel, "microgel") were examined in a second study in vitro with excised bovine udder skin and ex vivo with the isolated perfused bovine udder (Stahl et al 2012). The highest absorption (drug storage in the skin) was observed for the aqueous, enhancer-free solution and the gel containing the penetration enhancer 2-propanol, followed by the cream, which contained the permeation enhancer propylene glycol.…”
Section: The Influence Of Formulations On Drug Diffusion Into and Thrmentioning
confidence: 99%